Critical theory and human nature: Hartmut Rosa’s resonance theory from an evolutionary-anthropological perspective - Höffken, Ole (Acta academica (Bloemfontein, South Africa), 2024)
In one of the major contributions to current Critical Theory in the 21st century, Hartmut Rosa employs the notion of resonant subject-world-relationships to critically analyse structural features of modern societies that systematically undermine stable conditions for such relationships to unfold. The specific critical potential of resonance theory is based on its status as an account of the good life, which has to build on an account of human nature. Arguably, the best available account of human nature is given by evolutionary anthropology and psychology – proceeding from a wide notion of evolution as natural and cultural. I propose to complement resonance theory with evolutionary approaches to the question of the good life. Resonance theory can offer crucial refinements of the concept of the good life as presupposed by authors working within an evolutionary perspective, while in turn being able to profit from the empirical insights of evolutionary anthropology and psychology.